Differences in the development of the Szczecin Lagoon area in the Late Glacial and Holocene based on the geochemical analysis of carbonate sediments from Lake Nowowarpieńskie (NW Poland) - Strzelecka, Agnieszka; Wróbel, Rafał (Acta Geographica Lodziensia, 2021)
This paper presents the results of geochemical analysis performed for the more-than-10-m-long core of sediments derived from Lake Nowowarpieńskie. Contrary to what its geographical name would suggest, it is in fact a peripheral bay of the Szczecin Lagoon (NW Poland). A characteristic feature of the sedimentary cover of this water body is the several-metre-thick layer of lacustrine chalk, which is unique in the lithology of the sediments of today’s Szczecin Lagoon. This sediment has been analysed using atomic absorption spectrometry (AAS), energy-dispersive X-ray spectroscopy (EDS) and scanning electron microscopy (SEM) imaging. The chalk sediment from Lake Nowowarpieńskie is of chemical origin, bearing no fragments of vascular plants, but only traces of C-org in the form of small plant remains. The analysis of individual crystals using the EDS method also show Ca contents of over 99%. SEM images reveal that the sediment is characterised by a loose, disordered pack-ing of individual crystals, often combined to form aggregates with a tabular structure. The individual calcite grains are usually a few micrometres in size, while developed ones are mostly hypidiomorphic and show signs of corrosion. The sedimentation of the lacustrine chalk indicates that the post-glacial natural development of this part of what today constitutes Szczecin Lagoon differed from that of the rest of the lagoon. This sediment was deposited in a shallow but fertile isolated lake. The full profile of sediments from Lake Nowowarpieńskie reveals its distinct bipartite character, indicating two main stages of its evolution: carbonate and post-carbonate. In the first, the water body showed similarities to the neighbouring lakes of the Wkrzańska Plain. Its evolution was driven by climatic factors. The second stage was initiated by a palaeohydrological factor – Littorina transgression, which resulted in the lake being included into the hydrological system of the Szczecin Lagoon.